Handbook of energy audits - Thumann, Albert, ....-; Younger, William J., ....- (Lilburn : Fairmont, 2008)
1 - Energy Auditing Basics 2 - Energy Accounting and Analysis 3 - Understanding the Utility Bill 4 - Energy Economics 5 - Survey Instrumentation 6 - The Building Envelope 7 - The Electrical System Audit 8 - The Heating, Ventilating & Air Conditioning Audit 9 - Upgrading HVAC Systems for Energy Efficiency 10 - The Physical Plant Audit 11 - Central Plant Retrofit Considerations 12 - Maintenance & Energy Audits 13 - Self-Evaluation Checklists 14 - In Transition from Energy Audits to Industrial Assessments 15 - A Compendium of Handy Working Aids 16 - Computer Software for Energy Audits 17 - World Class Energy Assessments Software Directory, Glossary, Index
Keywords: Energiebeleid